Antioxidant and Antiproliferative Activity of Black Rice Extract Against Colon Cancer Cells In-Vitro and In-Silico - Alfarabi, Muhammad; Safithri, Mega; Cing, Jap Mai; Arodes, Evy Suryani; Andrianto, Dimas; Kurniasih, Rini; Hutapea, Helen Elisa Christin (Trends in Sciences, 2025)
Black rice is less popular for healthy use and not widely available in different parts of Indonesia. Only a few scientific reports are available on the health benefits of black rice, specifically with an integrated in-vitro and in-silico method for varieties present in the market, showing a need for investigations regarding bioactivity. Therefore, this analysis examines the bioactivity of black rice extracts of Cempo Ireng variety in-vitro and in-silico as a source of antioxidant and antiproliferation for colon cancer cells, along with determination of the compound content. The novelty was the integration of in-vitro and in-silico methods to explore the natural antioxidant sources and the inhibition of colon cancer cell proliferation from black rice of Cempo Ireng variety. Moreover, antioxidant activity was analyzed using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method. The 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay was conducted to determine antiproliferative activity, which was further examined in-silico with metabolites from black rice extract identified using gas chromatography–mass spectrometry (GC-MS) and liquid chromatography-high resolution mass spectrometry (LC-HRMS). The results indicated black rice extract had antioxidant activity to scavenge radicals. The activity had IC50 of 4.67 µg/mL for black rice chloroform (BRC) extract and 52.45 µg/mL for black rice ethanol (BRE) extract. Additionally, black rice extract can effectively inhibit the proliferation of colorectal cancer cells (8.28% - 9.10%). Metabolite groups detected in the extract included organic acids, flavonoids, terpenoids, phytosterols, amino acids, purines, organic alcohols, and organic bases. Campesterol and 24 - methylenecycloartanol were metabolites that had the best activity in inhibiting cancer treatment target proteins in-silico. This study showed the health benefits of black rice, suggesting the development of a functional food to support digestive health. HIGHLIGHTS Black rice extract of the Cempo Ireng variety was able to scavenge free radical. The extracts can inhibit cancer cell proliferation and are non-toxic to normal cells. Organic acids were the most frequently identified metabolites in black rice. Campesterol and 24 - methylenecycloartanol were the metabolites that had the best activity in inhibiting cancer therapy target proteins in-silico Black rice has a potential as a functional food that is effective as a natural antioxidant and can be used as an alternative treatment for colon cancer. GRAPHICAL ABSTRACT